2021
DOI: 10.3389/fpsyg.2021.804449
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Level of Physical Activity and Body Mass Index, and Quality of Life Among Elderly Women

Abstract: The process of aging leads to changes in functional abilities, fitness levels, level of physical activity, and body mass index (BMI), all of which causes changes in the quality of life. The current study aims to determine the association between the level of physical activity (PA) and BMI, and quality of life (QoL) among elderly women. The total sample numbered 156 women, with an average age of 67.7 ± 5.6 years. To determine the level of physical activity, the self-reported International Physical Activity Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 44 publications
0
7
1
Order By: Relevance
“…Furthermore, even the statistically significant associations differed from those established in previous research. Thus, no statistically significant associations were found between physical activity and physical health, contrary to the findings from earlier studies [14,48]. The data would be more understandable if the respondents were young, but this was a sample of middle-aged individuals.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Furthermore, even the statistically significant associations differed from those established in previous research. Thus, no statistically significant associations were found between physical activity and physical health, contrary to the findings from earlier studies [14,48]. The data would be more understandable if the respondents were young, but this was a sample of middle-aged individuals.…”
Section: Discussioncontrasting
confidence: 78%
“…However, some authors argue that the determination of whether physical activity enhances QoL is impossible because this construct cannot be effectively operationalized and assessed [12]. The positive associations between physical activity and perceptions of QoL vary depending on the domains of QoL assessed [13], as well as the intensity of physical activity [14]. Namely, in the working population, according to Puciato, Borysiuk, and Rozpara [15], physical activity of moderate and high intensity was positively associated with QoL, while in an elderly population, this association was only found with activities of moderate intensity [14,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This phenomenon should focus on BMI, because BMI is more important than weight and height can better show health problems, but neither of them can diagnose the health status of the individual [ 52 ], so it will not affect the detection results of the smart bracelet. The main difference lies in the BMI level of the participants; some studies have pointed out that the BMI of older adults is negatively correlated with walking distance [ 53 , 54 , 55 ]. Although there were differences in pre-retirement occupations between the males and females, they had all worked in society, had general social cognition, and could use the smart bracelets that were popular in the market.…”
Section: Discussionmentioning
confidence: 99%
“…They found that increased BMI is strongly correlated to decreased physical fitness [ 52 ]. Additionally, Ðošić et al elaborated that older women with a higher BMI scored better in the environmental than physical domains of quality of life [ 53 ]. In addition, Cárdenas et al found that high BMI is an important factor that may contribute to decreased physical activities and lead to serious health consequences [ 54 ].…”
Section: Discussionmentioning
confidence: 99%